Rectal treatment in ulcerative colitis; a qualitative study exploring reasons for under utilisation - Rothen, Jean-Pierre; Moerlen, Florence; von Büren, Céline; Allemann, Samuel; Arnet, Isabelle (Frontiers in Health Services, 2025)
IntroductionUlcerative colitis is an inflammatory bowel disease that is limited to the colon. First-line treatment consists of rectally administered suppositories, foam or enema. Adherence to rectal treatment is very low in people with ulcerative colitis. We aimed to explore modifiable factors influencing adherence to rectal treatment among patients, healthcare providers (HCP), and pharmaceutical companies, and to delineate new approaches to improve adherence to rectal medicines.MethodsWe recruited people using rectal treatment, community and clinical pharmacists, gastroenterologists, inflammatory bowel diseases (IBD) nurses, and representatives of pharmaceutical companies specialised in the production of rectal therapies. We performed semi-structured one-to-one interviews tackling the three pivotal topics knowledge and beliefs, product characteristics, and communication. We started with patient interviews whose statements served to inform the other interviews. All interviews were the subject of a keyword protocol, audio-recorded, and transcribed. Thematic analysis was used with inductive approach for the patients, and deductive approach for all other interviewees. Identified themes were compared and agreements and divergences were compiled.ResultsWe interviewed eight patients (22–77 years old, 3 women) in spring 2023, and stakeholders from the hospital (3 gastroenterologists and 2 IBD nurses), ambulatory setting (4 community pharmacists) and pharmaceutical companies (2 representatives) in 2024, all in the region of Basel (Switzerland). Overall, people with ulcerative colitis often feel left alone to cope with the challenges associated with their therapies. Pretreatment concerns and difficulties experienced by these people following their first attempts at use are not adequately addressed by HCPs. Training sessions for clinicians and pharmacists, patient-oriented demonstration materials, visual aids, and tips and tricks the application of rectal treatment could help improve the use of rectal medicines by people with ulcerative colitis.ConclusionThis study identified a detailed knowledge of the proper use of rectal treatment and frank communication between patients and HCPs as crucial for the adherence to rectally administered medicines. While these factors are broadly recognised in the literature, this study highlights their common priority among all stakeholders. In addition, solutions for future development and tailored interventions are proposed.